Building QoS Into Distributed Systems 1997
DOI: 10.1007/978-0-387-35170-4_33
|View full text |Cite
|
Sign up to set email alerts
|

QoS Mapping between User’s Preference and Bandwidth Control for Video Transport

Abstract: In this paper, we present a method of QoS mapping between user's preference on video quality and a required bandwidth to transport the video across the network. We first investigate the mapping method from QoS parameters to the required bandwidth on the network. For this purpose, we assume that the underlying network supports some bandwidth allocation mechanism, such as DBR service class in ATM, RSVP, IPv6 and so on. Then, for given QoS parameters in terms of spatial, SNR, and timely resolutions, the required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 9 publications
0
20
1
Order By: Relevance
“…-Formal QoS mappings have not been studied thoroughly so far. Some partial results can be found in [9] and [10].…”
Section: Related Workmentioning
confidence: 99%
“…-Formal QoS mappings have not been studied thoroughly so far. Some partial results can be found in [9] and [10].…”
Section: Related Workmentioning
confidence: 99%
“…Through experiments, it is shown that high-quality and TCP-friendly MPEG-2 video transfer can be performed with our proposed method. We take into account the relationship among quantizer scale, video rate and perceived video quality obtained in our research work on QoS mapping method for MPEG-2 video [14]. This is a good starting point of determining the control parameter appropriate for video rate adjustment with consideration of the perceived video quality.…”
Section: Fgs Video Coding Algorithmmentioning
confidence: 99%
“…In Fig.4, we depict an example of the relationship among the quantizer scale, the average video rate and the video quality in terms of SNR (Signal to Noise Ratio) when a video sequence is coded by MPEG-2 VBR coding algorithm where a static quantizer scale is applied to all pictures in a sequence [11]. The video sequence consists of 150 pictures of 704 480 pixels and the frame rate is 29.97 fps.…”
Section: Video Rate Controlmentioning
confidence: 99%
“…The video sequence consists of 150 pictures of 704 480 pixels and the frame rate is 29.97 fps. By applying the method proposed in [11], we can easily determine the appropriate quantizer scale to adjust the video rate to the estimated TCP throughput.…”
Section: Video Rate Controlmentioning
confidence: 99%